1994
DOI: 10.1128/aac.38.1.144
|View full text |Cite
|
Sign up to set email alerts
|

Comparative activities of piperacillin and tazobactam against clinical isolates of Legionella spp

Abstract: We evaluated the in vitro activity of piperacillin alone or in combination with the 1-lactamase inhibitor ,ug/ml; and piperacillin-tazobactam (expressed in terms of MIC of piperacillin) 0.5 and 1 (0.03 to 2) Rg/ml.Tazobactam alone and the combination with piperacillin were more active than piperacillin alone at the higher inoculum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
2
1

Year Published

1994
1994
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 14 publications
2
2
1
Order By: Relevance
“…Our studies confirm the excellent extracellular activities of tazobactam, clavulanate, piperacillin, and ceftriaxone against legionellae, as has been reported previously (1,20,28,31,36,38,39). All p-lactamase inhibitors studied have been reported to be active against extracellular Legionella spp., including sulbactam and BL-P2013, in addition to those reported in the present study (18).…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Our studies confirm the excellent extracellular activities of tazobactam, clavulanate, piperacillin, and ceftriaxone against legionellae, as has been reported previously (1,20,28,31,36,38,39). All p-lactamase inhibitors studied have been reported to be active against extracellular Legionella spp., including sulbactam and BL-P2013, in addition to those reported in the present study (18).…”
Section: Discussionsupporting
confidence: 72%
“…This has led to the evaluation of the activities of other P-lactamase inhibitors against L. pneumophila. Recently, Collins and colleagues (1) reported that tazobactam, with or without piperacillin, is active against extracellular Legionella species. We tested tazobactam alone and in combination with either ceftriaxone or piperacillin to confirm the findings of Collins and colleagues and to determine whether these antimicrobial agents were active against intracellular L. pneumophila.…”
mentioning
confidence: 99%
“…Erythromycin, probably the most widely used drug for treatment of Legionella pneumonia (14,27), inhibited all strains at Յ0.25 and Յ0.5 g/ml with the small and the large inocula, respectively. Those data were comparable to erythromycin A MICs obtained previously in our laboratory (7).…”
supporting
confidence: 90%
“…(25,34,36). At the smaller inoculum, 90% of the legionellae tested were inhibited by a 4-g/ml concentration of each drug, a concentration equivalent to MICs (7). Nevertheless, doxycycline showed activity against L. pneumophila in intracellular monocyte experiments when added at concentrations of 0.4 g/ml (20).…”
mentioning
confidence: 95%
“…The quantitative MIC was 0.016 g/ml. Our results showed a lower MIC than previous reports by Edelstein et al and Collins et al, which showed MICs between 0.12 and 1 g/ml and between 0.03 and 2 g/ml, respectively, reinforcing the effectiveness of these antibiotics against extracellular forms (4,5).…”
contrasting
confidence: 56%